Importance of the Use of the Internet of Things and its Implications in the Manufacturing Industry - Contreras, Laura; Perez, Juan (European Scientific Journal, ESJ, 2018)
The research presented in this paper is a literary analysis of 91 papers of 31 different journals of world recognition from different countries (England, Poland, Spain, China, Switzerland, Netherlands); focusing on productivity improvement inside a business through Internet of Things (IoT) in the manufacturing industry. It is essential to know the implications in the use of IoT for productivity improvement because IoT is having great influence in different context, one of them is businesses. The objective of this paper is to know the implications of the use of IoT to increase productivity, focusing on security and data privacy in the manufacturing sector. Suggestions are made regarding big data, digital manufacturing, the supply chain, cybersecurity, and monitoring and control systems for implementing IoT to improve productivity in a manufacturing industry. The use of new tools and technologies for improving productivity imply that the detailed aspects for its implementation must be analyze.